2020
DOI: 10.2215/cjn.06510619
|View full text |Cite
|
Sign up to set email alerts
|

Nonmedical Factors and Health-Related Quality of Life in CKD in India

Abstract: Background and objectives Patient-reported outcomes have gained prominence in the management of chronic noncommunicable diseases. Measurement of health-related quality of life is being increasingly incorporated into medical decision making and health care delivery processes. Design, setting, participants, & measurements The Indian Chronic Kidney Disease Study is a prospective cohort of participants with mild to moderate CKD. Baseline health-related quality of life scores, determined by the standardized Kidney … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 17 publications
3
4
0
4
Order By: Relevance
“…Meanwhile, the results of stepwise multiple regression models showed that financial burden was an independent predictor of QOL. This was consistent with the study of Modi et al 41 With the increase of medical insurance coverage in China, patients can reimburse most of expenses. However, for these patients with lower socioeconomic status, characterized by lower education, worse financial situation, or lack of employment, still cannot afford therapy, which can affect their adherence.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Meanwhile, the results of stepwise multiple regression models showed that financial burden was an independent predictor of QOL. This was consistent with the study of Modi et al 41 With the increase of medical insurance coverage in China, patients can reimburse most of expenses. However, for these patients with lower socioeconomic status, characterized by lower education, worse financial situation, or lack of employment, still cannot afford therapy, which can affect their adherence.…”
Section: Discussionsupporting
confidence: 92%
“…Meanwhile, the results of stepwise multiple regression models showed that financial burden was an independent predictor of QOL. This was consistent with the study of Modi et al 41 With the increase of medical insurance coverage in China, patients can reimburse most…”
Section: Discussionsupporting
confidence: 92%
“…The baseline characteristics show unique features that differentiate this population from patients with CKD enrolled in other cohort studies. Given the high and growing disease burden, a relatively rapid rate of progression, the high cost of care and the impact on quality of life [ 39 ], data from this study will provide important information to help the national strategy to manage CKD in India. In addition to defining outcomes and finding factors that associate with adverse outcomes in patients with CKD in low-resource settings, the ICKD study offers opportunities for international comparisons to further the goals of the global nephrology community.…”
Section: Discussionmentioning
confidence: 99%
“…The PF, RF, BP, and GH subscales were summarized in a physical component summary (PCS), while the VT, SF, RE and MH subscales were summarized in a mental component summary (MCS). We defined low HRQOL as an SF-36 score > one standard deviation (SD) below the mean, referring to previous studies with CKD patients 17 , 18 . Likewise, we defined low physical health and low mental health as PCS scores and MCS scores > one SD below the mean, respectively.…”
Section: Methodsmentioning
confidence: 99%